2011
DOI: 10.1080/09523987.2011.607321
|View full text |Cite
|
Sign up to set email alerts
|

International e-benchmarking: flexible peer development of authentic learning principles in higher education

Abstract: More and more, social technologies and virtual work methods are facilitating new ways of crossing boundaries in professional development and international collaborations. This paper examines the peer development of higher education teachers through the experiences of the IVBM project (International Virtual Benchmarking, 2009-2010. The e-benchmarking process in which teachers applied authentic learning criteria (Herrington & Oliver, 2000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…The results show that team dynamics comprises three stages: teambuilding, teamwork, and team performance (the TTT framework). These stages are similar to those theoretically described on the bases of previous research by Leppisaari et al (2009), which identifies four stages of virtual teams for successful performance: foundation and induction, incubation and socialization, improving performance/implementation, and outcomes. The last three can be discussed in relation to our empirical study results.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The results show that team dynamics comprises three stages: teambuilding, teamwork, and team performance (the TTT framework). These stages are similar to those theoretically described on the bases of previous research by Leppisaari et al (2009), which identifies four stages of virtual teams for successful performance: foundation and induction, incubation and socialization, improving performance/implementation, and outcomes. The last three can be discussed in relation to our empirical study results.…”
Section: Discussionsupporting
confidence: 69%
“…The teambuilding stage is similar to the incubation and socialization stage and includes in both models the processes of teambuilding, goal sharing, developing trust and commitment, and finding communication solutions. The teamwork stage is similar to the performance improvement stage in Leppisaari et al (2009), as both involve knowledge sharing, learning activities, and skills and communication. The final stage, team performance, is similar to the outcomes stage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, guidelines were developed to enhance scaffolding during the learning process. Leppisaari et al (2013) applied the elements of authentic learning identified by Herrington and Oliver (2000) to the evaluation of online courses. They found that the "multiple roles and perspectives" and "scaffolding" elements were achieved; however, the "collaborative construction of knowledge" and "authentic assessment" elements posed challenges (Herrington & Oliver 2000, pp.…”
Section: Previous Researchmentioning
confidence: 99%
“…The variety of roles in group work has been acknowledged as having a positive effect on innovation activities (Hero & Lindfors, 2019). Diversity refers to not only multiple professional roles and perspectives but also multiculturalism and a shared learning culture and understanding of the needs of others from different cultural backgrounds (Leppisaari et al, 2013;.…”
Section: ) Authentic Contextmentioning
confidence: 99%
“…Υπάρχουν, αντίστοιχα, πολυάριθμες έρευνες που εμπλέκουν φοιτητές σε διάφορα ακαδημαϊκά μαθήματα (Aviv et al 2003;Cohen et al, 2003;Vonderwell, 2003;Oι Sorensen & Murchu, 2004;Sorensen, 2005;Sorensen & Takle, 2006;Vesely et al, 2007;Black et al, 2008;Whipp & Lorentz, 2008;Chen et al, 2009;Rienties et al, 2009;Kucuk, 2010;Yang et al, 2010;Hou, 2011;Leppisaari et al, 2011;Ng et al, 2011;Pulford, 2011;Zhan et al, 2011;Kear et al, 2012;Kabilan & Khan 2012;Lu & Churchill, 2012;Zydney et al, 2012;Qiu & McDougall, 2013;Asoodar et. al., 2014;Tang & Lam, 2014;Wise et al, 2014).…”
Section: επισκόπηση πεδίουunclassified